2020
DOI: 10.1111/ene.14150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visual snow syndrome in the UK

Abstract: 44.8 AE 15 years), although this was not statistically different (P = 0.06). Of 22 participants with visual snow syndrome, 16 had mood symptoms (72.7%; P = 0.01), 12 had headache (54.5%; P = 0.06), including five with visual migraine aura (22.7%; P = 0.15) and 13 had tinnitus (59.1%; P < 0.001). No participant had diabetes or a cleft lip (control questions). Following a multivariable regression analysis to adjust for age and gender, only the association between visual snow syndrome and tinnitus remained signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 27 publications
4
88
0
Order By: Relevance
“…This devastating neurological condition is associated with the continuous perception of tiny dots in entire visual field, resembling snow. Kondziela et al found that the prevalence of visual snow syndrome is around 2% and revealed the association of this condition with tinnitus and headache, mostly migraine [48]. Another study not only confirmed this finding but also revealed that both tinnitus and migraine intensify visual snow by producing more additional visual symptoms [49].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This devastating neurological condition is associated with the continuous perception of tiny dots in entire visual field, resembling snow. Kondziela et al found that the prevalence of visual snow syndrome is around 2% and revealed the association of this condition with tinnitus and headache, mostly migraine [48]. Another study not only confirmed this finding but also revealed that both tinnitus and migraine intensify visual snow by producing more additional visual symptoms [49].…”
Section: Discussionmentioning
confidence: 88%
“…This scale is a survey with 25 items and divided into three subscales: functional, catastrophic, and emotional, with a total score ranging from 0 to 100. It grades five tinnitus severity categories: slight (0-16); mild (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); moderate (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56); severe (58-76); and catastrophic (78-100). Psychoacoustic characteristics of tinnitus, including its loudness and pitch, were measured using the standard clinical method by presenting sounds similar to those described by the patient [27,28].…”
Section: Tinnitusmentioning
confidence: 99%
“…They claimed that visual snow was a unique syndrome distinct from migraine, and the term visual snow syndrome (VSS) was subsequently introduced (2). VSS seems to be a common condition, with a recent study reporting a 2% prevalence in the general population (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the new study [1], the authors appropriately used the prevalence of cleft lip and diabetes in the UK as a positive control, and found them to be consistent in their cohort. However, the prevalence of migraine (33.4%) and of migraine visual aura (10.9%) are substantially higher than expected from a UK population‐based study: 1‐year prevalence of migraine 14.3%, aura 5.8% [8].…”
Section: What Does the Epidemiology Of Visual Snow Tell Us?mentioning
confidence: 99%
“…In general, the condition seems non‐progressive; this is what a gathering of the North American Neuro‐Ophthalmological Society made clear to one of us (PJG) in January 2005, and seems reinforced by the UK population study [1]. When we look at a large population of patients with VSS, there is a range of severity [9].…”
Section: What Should We Tell Patients?mentioning
confidence: 99%